The Impact of Natural Disasters on Maternal Health: Hurricanes Irma and María in Puerto Rico - Irene Lafarga Previdi; Michael Welton; Jazmín Díaz Rivera; Deborah J. Watkins; Zulmarie Díaz; Héctor R. Torres; Chrystal Galán; Natacha I. Guilloty; Luis D. Agosto; José F. Cordero; Akram Alshawabkeh; Carmen M. Vélez Vega (MDPI AG, 2022)
The PROTECT research Center funded by the NIH's National Institute of Environmental Health Sciences (NIEHS) Superfund Research Program was launched in 2010 to explore the impact of exposure to pollutants on the high rate of premature births in Puerto Rico. In September 2017, Hurricanes Irma and María devastated the archipelago, which caused: collapse of the electrical system, collapse of the communication system, limited access to clean water, food, gas, and health services, destruction of public (e.g., hospitals) and private property (e.g., houses) and more than 4500 deaths. Pregnant and postpartum individuals are especially vulnerable to natural disasters. They face difficulty obtaining adequate pre- and post-natal care, are exposed to increased risk of miscarriage, premature delivery, and giving birth to low birth weight babies during and after disasters and are also more likely to suffer physical and mental health problems compared to the general population during and after disasters. A face-to-face questionnaire was administered to PROTECT participants who were pregnant during hurricanes Irma or Maria or who became pregnant shortly after in order to identify hurricane-related sources of stress and other adverse effects. This paper is based on the answers to the open-ended question at the end of the questionnaire where participants were asked to share their experiences during and after the hurricanes. Among the 375 participants who completed the survey, 76 answers to the open-ended question were considered due to data saturation. The answers to the open-ended question were transcribed into a document in order to facilitate the coding process. The transcribed text was analyzed first to identify emerging categories and then coded to identify common themes as well as divergence among participants. The following themes were identified: pregnancy and birth challenges, lack of access to basic services, housing conditions, stressful working conditions, concerns about health, concerns about their children, and positive or protective aspects. The results indicate how the disruption in access to basic services has a unique impact on the physical and mental health of pregnant and post-partum women in an emergency situation. These findings point to the potential benefit of developing specific protocols designed for emergency preparedness aimed at this population, which can inform healthcare providers and community organizations in case of future events.